2010
DOI: 10.5194/acpd-10-24853-2010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Middle atmosphere response to the solar cycle in irradiance and ionizing particle precipitation

Abstract: The impact of NO<sub>x</sub> and HO<sub>x</sub> production by three types of energetic particle precipitation (EPP), aurora, solar proton events and galactic cosmic rays is examined using a chemistry climate model. Ensemble simulations forced by transient EPP derived from observations with one-year repeating sea surface temperatures and fixed chemical boundary conditions were conducted for cases with and without solar cycle in irradiance. Our model results show a wintertime polar strato… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 82 publications
3
44
0
Order By: Relevance
“…Codrescu et al 1997;Semeniuk et al 2011) or from semiempirical geomagnetic activity-based parameterisations for NO x production (Baumgaertner et al 2009;Rozanov et al 2012), although the latter responds strongly not just to NO x produced by EPP in the upper mesosphere, but also to NO x produced by EPP in the thermosphere and transported downwards Holt et al 2012;Funke et al 2014). The use of the POES observations also has problems as highlighted by Rodger et al (2010): During geomagnetically disturbed times, i.e.…”
Section: Energetic Particle Precipitationmentioning
confidence: 99%
See 3 more Smart Citations
“…Codrescu et al 1997;Semeniuk et al 2011) or from semiempirical geomagnetic activity-based parameterisations for NO x production (Baumgaertner et al 2009;Rozanov et al 2012), although the latter responds strongly not just to NO x produced by EPP in the upper mesosphere, but also to NO x produced by EPP in the thermosphere and transported downwards Holt et al 2012;Funke et al 2014). The use of the POES observations also has problems as highlighted by Rodger et al (2010): During geomagnetically disturbed times, i.e.…”
Section: Energetic Particle Precipitationmentioning
confidence: 99%
“…The results suggested that a major future event of similar scale could potentially impact the total ozone levels in polar regions with reductions of up to 20 DU. Further work with two different CCMs was done to evaluate the wider effects from CR (also including EPP) (Rozanov et al 2012;Semeniuk et al 2011;Calisto et al 2011). A review by Rozanov et al (2012) examining the potential impacts on both atmospheric chemistry and some climate variables concluded that at least in the model (CCM SOCOL), the combined effects of GCR, SPEs and EEP can potentially affect not just the chemical composition but atmospheric dynamics as well.…”
Section: Cosmic Raysmentioning
confidence: 99%
See 2 more Smart Citations
“…This captures some of the EPP indirect effect but not all. Increases in NOy transported into the lower stratosphere could survive from the previous winter to the following summer and fall (Orsolini 2001;Orsolini et al 2003) and contribute to the ozone loss in early winter because of a long lifetime of NOy there (Semeniuk et al 2011). This process may have an impact on polar vortex formation during its early stage in late fall and early winter.…”
Section: Discussionmentioning
confidence: 99%